Low-density hepatitis C virus infectious particles are protected from oxidation by secreted cellular proteins - Granier, Christelle; Toesca, Johan; Mialon, Chloé; Ritter, Maureen; Freitas, Natalia; Boson, Bertrand; Pécheur, Eve-Isabelle; Cosset, François-Loïc; Denolly, Solène (mBio, 2023)
Hepatitis C virus (HCV) particles secreted from cells are stable at 37°C, whether the producer cell media contain serum or not. Yet, we found that intracellular HCV particles harvested after freeze-thawing of producer cells are highly unstable upon resuspension in a serum-free medium, indicating that either HCV particles gain intrinsic stability during their secretion and egress from producer cells or, alternatively, that a factor secreted from cells can stabilize intrinsically unstable HCV particles. We aimed at investigating either possibility and unraveling the mechanisms evolved by HCV to promote the stability of its viral particles. We showed that after purification and resuspension in a serum-free medium, HCV infectious particles released in cell supernatants are quickly and specifically degraded at 37°C in comparison to other viruses that can infect hepatic cells. We also found that cell-secreted proteins, including human serum albumin and transferrin, could protect HCV particles from this loss of infectivity. Moreover, we showed that such protection mainly impacted low-density particles (d < 1.08), suggesting a specific alteration of viral particles that are lipidated. Since we also demonstrated that neither HCV RNA nor surface glycoproteins were altered, this suggested that virion lipids are sensitive to decay, resulting in a loss of infectivity. Indeed, our results further indicated that HCV particles are sensitive to oxidation, which leads to a loss of their membrane fusion capacity. Altogether, our results indicate that HCV is highly sensitive to oxidation and highlight a specific protection mechanism evolved by HCV to prevent oxidation-mediated degradation of its lipidated particles by using secreted factors.